2018
DOI: 10.1534/genetics.118.301550
|View full text |Cite
|
Sign up to set email alerts
|

Incompatibilities in Mismatch Repair Genes MLH1-PMS1 Contribute to a Wide Range of Mutation Rates in Human Isolates of Baker’s Yeast

Abstract: Laboratory baker's yeast strains bearing an incompatible combination of MLH1 and PMS1 mismatch repair alleles are mutators that can adapt more rapidly to stress, but do so at the cost of long-term fitness. We identified 18 baker's yeast isolates from 1011 surveyed that contain the incompatible MLH1-PMS1 genotype in a heterozygous state. Surprisingly, the incompatible combination from two human clinical heterozygous diploid isolates, YJS5845 and YJS5885, contain the exact MLH1 (S288c-derived) and PMS1 (SK1-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…The DNA sequencing of natural isolates of yeast strains, which tend to preferentially undergo asexual reproduction, revealed ~63% heterozygosity, suggesting some fitness advantage for this condition 42 . Higher levels of heterozygosity in yeast are observed under diverse stress conditions, such as exposure to the antifungal drug fluconazole, growth at high temperature, or incompatibility of the mismatch repair genes MLH1-PMS1 43 , 44 .…”
Section: Second-line Adaptive Mechanismsmentioning
confidence: 99%
“…The DNA sequencing of natural isolates of yeast strains, which tend to preferentially undergo asexual reproduction, revealed ~63% heterozygosity, suggesting some fitness advantage for this condition 42 . Higher levels of heterozygosity in yeast are observed under diverse stress conditions, such as exposure to the antifungal drug fluconazole, growth at high temperature, or incompatibility of the mismatch repair genes MLH1-PMS1 43 , 44 .…”
Section: Second-line Adaptive Mechanismsmentioning
confidence: 99%
“…Conservation of a response that allows pathogens to adopt hypermutator states with minimal fitness cost could be beneficial for evolution over short and long timescales. Indeed, many microbial pathogens, and even wild fungal populations, frequently adopt a hypermutator state (Bui et al, 2017;Guo et al, 2018;Raghavan et al, 2018). The alleles that govern this behavior have been retained across a considerable evolutionary distance (Bui et al, 2017), suggesting that it confers an adaptive advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Incompatibilities in the mismatch repair components Mlh1 and Pms1 have also been reported to contribute to hypermutation in S. cerevisiae laboratory strains 46 , 47 . Studies have identified several S. cerevisiae strains isolated from humans that encode these same MLH1 - PMS1 incompatible alleles 48 . Although the S. cerevisiae diploids with incompatible alleles isolated from humans were not hypermutators themselves, their meiotic progeny displayed a wide range of mutation rates and included hypermutators, thus providing an opportunity to produce progeny with variable fitness under stressful conditions 47 , 48 .…”
Section: Small-scale Evolution Of Fungal Genomesmentioning
confidence: 99%
“…Studies have identified several S. cerevisiae strains isolated from humans that encode these same MLH1 - PMS1 incompatible alleles 48 . Although the S. cerevisiae diploids with incompatible alleles isolated from humans were not hypermutators themselves, their meiotic progeny displayed a wide range of mutation rates and included hypermutators, thus providing an opportunity to produce progeny with variable fitness under stressful conditions 47 , 48 . Another mechanism of hypermutation caused by a mutation in a DNA polymerase delta subunit was also described in C. neoformans ; this mechanism of hypermutation resulted in genome-wide increases in transition and transversion mutations but reduced viability and virulence 49 , 50 .…”
Section: Small-scale Evolution Of Fungal Genomesmentioning
confidence: 99%